A Taste of Earth - I. - O.P.E.R.A. 3D, Mariakerke; ARKUMEKO, Gent (Mariakerke : O.P.E.R.A. 3D, 1991)
Delbroek, Jos ; De Roover, Marc ; Massart, Jean-Georges ; Verschueren, Bob
A Taste of Earth - I, Beukenhof, Gent/Mariakerke, 12/X - 30/XI/1991. A Taste of Earth - I is een realisatie van O.P.E.R.A. 3D naar een concept van ARKUMEKO.
boek